2014
DOI: 10.1292/jvms.13-0156
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib Responsiveness in Canine Mast Cell Tumors Carrying Novel Mutations of <i>c-KIT</i> Exon 11

Abstract: In 2 individual cases of canine mast cell tumors, we identified 2 novel c-KIT mutations in exon 11: a 9-base pair (bp) deletion (c.1663-1671del) and a point mutation (c.1676T>A). The 9-bp deletion mutation caused a loss of 3 amino acids, corresponding to p.Gln555_Lys557del, and the point mutation resulted in the substitution of valine by aspartic acid (p.Val559Asp) in the juxtamembrane domain of the protein. Imatinib mesylate, a therapeutic agent for canine mast cell tumors, was used to treat both tumors. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 11 publications
0
17
0
1
Order By: Relevance
“…For the control of MCTs carrying c-kit exon 8 and 11 mutations, several previous studies have shown that TKIs can be effective, and imatinib has recently begun to be utilised for canine MCT as a novel targeted therapy (Kobayashi et al 2012;Nakano et al 2014). Imatinib is a commercially available drug targeting tyrosine kinases, and it inhibits downstream signalling of KIT by competing with adenosine triphosphate (ATP) for the ATP binding site (Buchdunger et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For the control of MCTs carrying c-kit exon 8 and 11 mutations, several previous studies have shown that TKIs can be effective, and imatinib has recently begun to be utilised for canine MCT as a novel targeted therapy (Kobayashi et al 2012;Nakano et al 2014). Imatinib is a commercially available drug targeting tyrosine kinases, and it inhibits downstream signalling of KIT by competing with adenosine triphosphate (ATP) for the ATP binding site (Buchdunger et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations consisting of internal tandem duplication (ITD) within c-kit exons 8 and 11, which causes ligand-independent phosphorylation of KIT, have been frequently found in highgrade MCT in dogs (London et al 1999;Downing et al 2002;Zemke et al 2002;Webster et al 2006;Kobayashi et al 2012). It has been reported that canine MCT with these mutations in the exon 8 and exon 11 regions regressed after treatment with imatinib in xenografted severe combined immunodeficiency (SCID) mice and dogs with spontaneous MCT (Kobie et al 2007;Kobayashi et al 2012;Nakano et al 2014). Moreover, other studies reported that several TKIs with different chemical structures from imatinib induced objective tumour regression in canine MCTs with these mutations Hahn et al 2008;London et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In dogs, a total of 28 cases of MCTs treated with imatinib have been reported; of these, 25 cases were treated with imatinib (10-12.7 mg/kg daily), with examination of KIT mutation status (examination of entire KIT, KIT exons 8, 9 and 11, or KIT exon 11 alone) (Isotani et al, 2008;Yamada et al, 2011;Kobayashi et al, 2012;Nakano et al, 2014). In addition to these 25 cases, we have treated 13 cases with imatinib (10-12 mg/kg daily) with examination of KIT mutation status (KIT exons 8, 9, and 11) (unpublished data).…”
Section: Mast Cell Tumoursmentioning
confidence: 99%